IREC2015 the Sixth International Renewable Energy Congress 2015
DOI: 10.1109/irec.2015.7110920
|View full text |Cite
|
Sign up to set email alerts
|

Size and grain-boundary effects on the performance of polycrystalline CIGS-based solar cells

Abstract: This work reviews the effect of Geometrical, physical and electrical parameters of the polycristalline CIGS thin film used as absorber materials in substrate CuIn 0.7 Ga 0.3 Se 2 (CIGS) solar cells. Two-dimensional device simulator Atlas SILVACO-TCAD was employed to study the performances of ZnO:Al/CdS/CIGS/Metal solar cell structure. The impacts of the grain sizes and the grain boundaries (GBs) in the polycrystalline p-CIGS absorber layer have been investigated. The variation of grain sizes in the CIGS bulk w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…[46][47][48] The process also enlarges grain size, which effectively decreases grain boundary concentration, potentially boosts carrier mobility, reduces the chance of electron-hole recombination, and subsequently increases current generation. [49][50][51] The next section discusses the development of a molecular-based approach for CIGSe PV devices using the thiol-amine solvent combination. Table I summarizes the recent PV performance of processed CIGSe thin-film devices fabricated using the thiol-amine route.…”
mentioning
confidence: 99%
“…[46][47][48] The process also enlarges grain size, which effectively decreases grain boundary concentration, potentially boosts carrier mobility, reduces the chance of electron-hole recombination, and subsequently increases current generation. [49][50][51] The next section discusses the development of a molecular-based approach for CIGSe PV devices using the thiol-amine solvent combination. Table I summarizes the recent PV performance of processed CIGSe thin-film devices fabricated using the thiol-amine route.…”
mentioning
confidence: 99%
“…This was suggested to be due to the formation of different defects in grain boundaries, both donor and acceptor type that create a potential well in the band structure, though the width of these wells was found to be around 1-2 nm. Grain boundaries were also studied with simulation tools, such as in [Idris, 2015], in which a CIGS solar cell with a grain boundary is simulated. Different properties related to the grain boundary, such as the width of the grain or the width of the grain boundary were varied, and it was found that larger grain sizes correlate with increased efficiencies while larger grain boundary widths are related to lower efficiencies [Idris, 2015].…”
Section: Performance Loss Mechanisms In Cellsmentioning
confidence: 99%
“…Grain boundaries were also studied with simulation tools, such as in [Idris, 2015], in which a CIGS solar cell with a grain boundary is simulated. Different properties related to the grain boundary, such as the width of the grain or the width of the grain boundary were varied, and it was found that larger grain sizes correlate with increased efficiencies while larger grain boundary widths are related to lower efficiencies [Idris, 2015].…”
Section: Performance Loss Mechanisms In Cellsmentioning
confidence: 99%